The effect of administrative transparency in the maintenance of public money - An empirical study on administrative employees at King Abdul-Aziz University Hospital in Jeddah - Zaki, Khadija Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to identify the administrative employees’ perspectives at King Abdul-Aziz University Hospital regarding the effect of administrative transparency in the maintenance of public money. The study was conducted on a simple random sample of 216 administrative staff at King Abdul-Aziz University Hospital. The data were collected by distributing a questionnaire consisting of three parts: the first part included the demographic data of the respondents, the second part included (20) items to measure the dimensions of administrative transparency. The third part included (11) items to measure the degree of preservation of public money in King Abdul-Aziz University Hospital in Jeddah. The descriptive analytical method and statistical data analysis were used using the statistical packages for social sciences program (SPSS). The main findings of the study were as follows: There was a homogeneity in the opinions of the respondents on the dimensions of the axis of participation. The results showed that the participation dimension is applied at King Abdul Aziz University in Jeddah to a moderate degree, while both the information and the accountability dimensions in the King Abdul Aziz University Hospital are applied to a great extent on the Likert scale. The study also showed that the general average of the elements of the employees’ awareness of the rules and regulations of maintaining the public money in the hospital showed a high and average (4.102). The study recommended several recommendations, most important of which are: To activate the role of participation as one of the dimensions of administrative transparency by establishing an effective communication system that ensures communication with employees at all administrative levels, as well as encouraging the participation of staff in developing and reviewing strategic plans at the hospital. In addition to supporting the management of information systems to provide more information protection programs to ensure that they are not lost or compromised in a way that does not conflict with transparency. As well as activate the mechanisms of administrative accountability in the Hospital of King Abdul-Aziz University in Jeddah and announced to all employees to be reviewed and monitored constantly and applied to all without prejudice. It also recommended the need to coordinate the efforts between the SAIs and the executive bodies at the university to raise awareness of the importance and ways of enhancing the preservation of public money.